PENGARUH EFEKTIVITAS SIA, LINGKUNGAN KERJA FISIK DAN INSENTIF TERHADAP KINERJA INDIVIDU PENGGUNA SIA PADA LPD DI KECAMATAN ABIANSEMAL - I Gusti Ayu Wilan Dewi; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2022)
The achievement of an organization or association can be seen from the exhibition of every person. The organization or association anticipates that employees should have the option to finish their jobs well and produce data in an ideal and exact way. The motivation behind this review is to discover the impact of the viability of bookkeeping data frameworks, actual workplaces and impetuses on the singular presentation of clients of bookkeeping data frameworks at town credit foundations in Abiansemal subdistrict. The example in this review was 34 LPD in Abiansemal District with a sum of 102 respondents. The inspecting technique in this review utilized purposive examining. The information investigation procedures utilized are legitimacy test, unwavering quality test, old style suspicion test, numerous straight relapse examination, assurance coefficient (R2), F test and t test. The aftereffects of this review showed that the adequacy of bookkeeping data frameworks affects the singular presentation of clients of bookkeeping data frameworks, the actual workplace influences the singular exhibition of clients of bookkeeping data frameworks and motivating forces have no impact on the singular presentation of clients of bookkeeping data frameworks.